2015
DOI: 10.14393/bj-v31n1a2015-15069
|View full text |Cite
|
Sign up to set email alerts
|

Citotoxicidade das águas do Rio do Peixe (São Paulo-Brasil), em células meristemáticas de raiz de Allium cepa L.

Abstract: RESUMO: Nas últimas décadas, a qualidade da água do Rio do Peixe, localizado no interior do Estado de São Paulo, está diminuindo, principalmente porque o rio vem sofrendo com o desmatamento feito às suas margens, o que provocou o assoreamento e permitiu o despejo de todos os tipos de resíduos, em especial das indústrias que ficam ao seu redor. Assim, o objetivo deste trabalho foi avaliar o potencial citotóxico das águas do Rio do Peixe, coletadas em quatro propriedades rurais localizadas em Garça-SP (nascente)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
2
0
2
Order By: Relevance
“…The Chromosomal changes observed (Figure 3) were mainly colchicine, disorganized metaphases, multipolar anaphases and with loss of chromosomes. These results are similar to those observed by Costa, Domingues, Düsman, Almeida, and Vicentini (2015) who analyzed the water of Rio do Peixe (São Paulo), and by Maschio (2009) who examined the water from Municipal Dam of São José do Rio Preto (SP). In spite of the alterations observed, those studies did not evidence cytotoxic characteristics in samples, which corroborates with the present study.…”
Section: Toxicological Testssupporting
confidence: 88%
See 1 more Smart Citation
“…The Chromosomal changes observed (Figure 3) were mainly colchicine, disorganized metaphases, multipolar anaphases and with loss of chromosomes. These results are similar to those observed by Costa, Domingues, Düsman, Almeida, and Vicentini (2015) who analyzed the water of Rio do Peixe (São Paulo), and by Maschio (2009) who examined the water from Municipal Dam of São José do Rio Preto (SP). In spite of the alterations observed, those studies did not evidence cytotoxic characteristics in samples, which corroborates with the present study.…”
Section: Toxicological Testssupporting
confidence: 88%
“…According to Costa et al (2015) these types of chromosomal alterations are due to changes in the formation process of spindle fibers, which prevent equatorial plate organizing and chromosomes to be separated correctly during anaphase. That indicates the presence of eugenic substances (Oliveira, Voltolini, & Barbério, 2011), influenced by toxic compounds that had contact with organisms such as heavy metals and agrochemical compounds (Maschio, 2009;Peron, Canesin, & Cardoso, 2009).…”
Section: Toxicological Testsmentioning
confidence: 99%
“…The absence of A. cepa cytotoxicity, was also found in waters contaminated with petrochemical derivatives (leaked from a pipeline) (Leme and Marin-Morales, 2008) and effluents from refineries (Gupta and Ahmad, 2012). Similar results, using the same test system as the present study, were found on the surface waters of the Sava River (Croatia) (Radic et al, 2010), on the waters from Ribeirões Varginha River (Califórnia-Paraná-Brazil) and Tabatinga Juan Camilo Pires Salcedo Restrepo et al River (Mandaguari-Paraná-Brasil) (Ferreira et al, 2012), and on the waters from the Peixe River collected in the cities of Garça, Tupã, Flórida Paulista and Ouro Verde (São Paulo-Brazil) (Costa et al, 2015), which also received agricultural, industrial and urban effluents along their courses. Morphological changes and chromosomal alterations were also not observed when exposed to the waters of Trincheira´s River, similar to work by Ferreira et al (2012).…”
Section: Resultssupporting
confidence: 64%
“…It is a fact that the use and occupation of the land interfere with the quality of a water body, and this interference does not occur only in a localized way, but reaches the whole region that surrounds it (Oliveira et al, 2012;Costa, et al, 2015). Thus, proximity analyses are valuable to detect the use and occupation of the land around the sampling points and to assist in the evaluation of water quality.…”
Section: Introductionmentioning
confidence: 99%